A comparative study on the physicochemical properties and gastrointestinal delivery of calcium niosomes produced by low and high-energy techniques - Jorge Alejandro Barbosa-Nuñez; Sara Elisa Herrera-Rodríguez; Eristeo García-Márquez; Hugo Espinosa-Andrews (Elsevier, 2024)
Since the bioavailability of calcium from foods and supplements is low, its encapsulation in niosomes is proposed as a potential solution to this issue. This study aimed to compare the physiochemical properties and release profiles of niosomes with calcium chloride and calcium lactate produced by injection and sonication methods. The size distribution (200-300 nm), encapsulation efficiency (20-40 %), stability, release profile, cytotoxicity, and calcium bioavailability of the niosomes were characterized. The production method, rather than the calcium salt used, impacted the properties of the niosomes. Calcium release under gastrointestinal conditions was dependent on both the calcium source and the production method, which was characterized by a Peppas-Sahlin release model. Calcium niosomes were not cytotoxic to intestinal cells. All the calcium niosomes showed high bioavailability in cells (5-20 % greater than the control) but lower bioavailability than the non-encapsulated calcium salts (80-110 % above control) due to their high solubility. Nevertheless, the use of niosomes might be a promising approach for improving calcium bioavailability.